Impacto de la inteligencia emocional sobre el liderazgo: revisión aplicada - Aguirre Prada, Mayra Alejandra (2023)
Emotional intelligence is a central psychological factor for leadership in companies, due to the bond it provides between leaders and followers (Torrence y Connelly, 2019). The aim of thisstudy is to review the impact of emotional intelligence on leadership, through A systematic review was carried outfollowing the procedures ofthe PRISMA guideline (Page, et al., 2022). On the other hand, the databases used were Scopus and Proquest, and the studies that evaluated the impact of emotional intelligence on leadership in organizational processes were selected (n=10). For quality analysis, critical reading and study evaluation were used. The methodology of the selected studieswascorrelationalanalysis betweentheresultsofthescalesthatmeasured the variables. In general,studies where the impact of emotional intelligence on leadership was evidenced were found. For future research, it is recommended thatexperimentalproceduresandmethodologiesare improved.